Hubungan Antara Perubahan Fisik dengan Kecemasan pada Wanita Menopause di Desa Pupua - Putu Asih Primatanti; Putu Arya Suryanditha; Ayu Krisma Yanti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Women who experience menopause are described as experiencing many problems, among others, experiencing physical and psychological changes such as anxiety. The study aimed to determine the relationship between physical changes and anxiety in menopausal women in Pupuan Village. Respondents in this study were women who had experienced menopause who lived in Pupuan Village. This research is a quantitative research with a survey design (non-experimental). The data were collected in a cross sectional manner, because the measurement of the independent and dependent variable was carried out simultaneously. The sampling technique was done by purposive sampling with a minimum sample size of 82 people. Data were collected using the Hamilton Rating Scale of Anxiety (HRS-A) questionnaire. The results showed that most respondents experienced physical changes in the moderate category as many as 38 people (46.3%). As for the level of anxiety, the majority of respondents experienced moderate category anxiety as many as 30 people (36.6%). Based on the Chi-Square analysis test result, a significance score of 0.027 (<0.05) was obtained. It can be concluded that there is a significant relationship between physical changes and anxiety.